4(x-3)+x=2x+1/2(6x-12)

Simple and best practice solution for 4(x-3)+x=2x+1/2(6x-12) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(x-3)+x=2x+1/2(6x-12) equation:



4(x-3)+x=2x+1/2(6x-12)
We move all terms to the left:
4(x-3)+x-(2x+1/2(6x-12))=0
Domain of the equation: 2(6x-12))!=0
x∈R
We add all the numbers together, and all the variables
x+4(x-3)-(2x+1/2(6x-12))=0
We multiply parentheses
x+4x-(2x+1/2(6x-12))-12=0
We multiply all the terms by the denominator
x*2(6x-12))+4x*2(6x-12))-(2x+1-12*2(6x-12))=0
We add all the numbers together, and all the variables
x*2(6x-12))+4x*2(6x-12))-(2x+1-12*2(6x=0
Wy multiply elements
4x^3(6-12))-(2x-12*2(6x+1=0
We do not support expression: x^3(6

See similar equations:

| 90+30+4x-4=180 | | 3/10+5x=11 | | j/8-17=-11 | | Y-6=2(3x4) | | 4(x-5)=3x+10 | | |3x-6|=30 | | -12+k=17 | | 8(a+2)+3=27 | | 2s-2=1.52 | | 2(6x+)=-(x-4) | | -2{3x-1}-4x+3=23 | | F(-2)=13x-4 | | 9p-9p=0 | | 3w+6=5w-6 | | 6/5=v/5 | | 42=60x | | 5(a-2)=25 | | 21.81=3.12x+96.69 | | -14-5=-10x-45 | | 4y×4y+3y=10×100 | | j/9-2=2 | | g/3-1.4=2.61 | | v=17+4•4 | | (8x+20)=56 | | 2(5x+3)=7x–8 | | 6/5=5/v | | 5-6+x=4x+10 | | 5(-4q+3)=-2q-3 | | 40÷5/4=x | | 13x+37=1+5x | | -3=w/4-6 | | 4(-a+2)+2(5a-3)=2a+4(a+5) |

Equations solver categories